Spectroscopic binaries in southern open clusters - Levato, Orlando Hugo (2004)
This is a report on an ongoing program about binaries in southern open clusters. The long-term purpose of this project is to contribute to understanding the formation and evolution of spectroscopic binaries, providing observational constraints that will permit tests of some of the current theories on binary formation in open clusters.